2008
DOI: 10.11646/zootaxa.1888.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Variability in trunk segmentation in the centipede order Scolopendromorpha: a remarkable new species of Scolopendropsis Brandt (Chilopoda: Scolopendridae) from Brazil

Abstract: Of the two centipede orders that complete segmentation during embryogenesis, most species belonging to Geophilomorpha have an intraspecifically variable number of trunk segments, whereas those of the Scolopendromorpha have been assumed to have a fixed segment number, with minor variation (21 or 23 segments) across the group as a whole. Trunk segment numbers are used as a taxonomic character as high as the familial or subordinal level in Scolopendromorpha. The first known instance of variability in trunk segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…Centipedes of the order Scolopendromorpha exhibit minor interspecific variability in segment numbers; until recently all known species had either 21 or 23 leg-bearing trunk segments (Chagas-Junior et al 2008). Segment number appeared to be very conserved and was given considerable taxonomic weight, until investigations on the Brazilian Scolopendropsis bahiensis revealed that is has either 21 or 23 segments in different parts of its geographic range.…”
Section: Duplication Of Segments In a Centipedementioning
confidence: 99%
See 1 more Smart Citation
“…Centipedes of the order Scolopendromorpha exhibit minor interspecific variability in segment numbers; until recently all known species had either 21 or 23 leg-bearing trunk segments (Chagas-Junior et al 2008). Segment number appeared to be very conserved and was given considerable taxonomic weight, until investigations on the Brazilian Scolopendropsis bahiensis revealed that is has either 21 or 23 segments in different parts of its geographic range.…”
Section: Duplication Of Segments In a Centipedementioning
confidence: 99%
“…Segment number appeared to be very conserved and was given considerable taxonomic weight, until investigations on the Brazilian Scolopendropsis bahiensis revealed that is has either 21 or 23 segments in different parts of its geographic range. This surprising finding was even much topped by the identification of a new species, Scolopendropsis duplicata, which is closely related to S. bahiensis, but differs from its putative sister species in that it has either 39 or 43 rather than 21 or 23 segments (Chagas-Junior et al 2008). The authors do not speculate on the developmental genetic basis of their remarkable finding, but a gain-of-function mutation in something resembling the pair-rule genes involved in the embryogenesis of the fruit fly D. melanogaster comes to mind.…”
Section: Duplication Of Segments In a Centipedementioning
confidence: 99%
“…In the Scolopendromorpha, the sister‐group of the Geophilomorpha, which includes about 700 species (Bonato, ), there is an interesting case of possible LBS number evolution by macromutation. All but one species of scolopendromorph have either 21 or 23 LBS; but the one that does not ( Scolopendropsis duplicata ; Chagas‐Junior, Edgecombe & Minelli, ) has 39/43 LBS (the difference probably being due to sexual dimorphism). We suspect that this kind of change in LBS number is the exception rather than the rule; and that most changes in LBS number that occur in arthropods are due to a transient period of limited intraspecific variation in normally invariant groups caused by a period of extreme environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although we suspect that a smallish shift in the segment number distribution is what happens in the ''typical'' geophilomorph speciation event, not all speciations in the group may be restricted to such relatively minor changes in this variable. The recent discovery in the Scolopendromorpha (the sister group to Geophilomorpha) of the remarkable species Scolopendropsis duplicata, which seems to have undergone an approximate doubling of segment number in a single speciation event (Chagas-Junior et al 2008), suggests caution in this respect. Large changes in segment number may also have taken place in the evolution of some families within the Geophilomorpha (Bonato et al 2003).…”
Section: Discussionmentioning
confidence: 99%